2019
DOI: 10.1136/emermed-2018-208133
|View full text |Cite
|
Sign up to set email alerts
|

Process conformance is associated with successful first intubation attempt and lower odds of adverse events in a paediatric emergency setting

Abstract: BackgroundIntubation is an essential, life-saving skill but associated with a high risk for adverse outcomes. Intubation protocols have been implemented to increase success and reduce complications, but the impact of protocol conformance is not known. Our study aimed to determine association between conformance with an intubation process model and outcomes.MethodsAn interdisciplinary expert panel developed a process model of tasks and sequencing deemed necessary for successful intubation. The model was then re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…We did observe a high rate of equipment failures as well as an association of equipment failures with TIAEs. Quality improvement initiatives may improve success rates and reduce TIAEs ( 15 ). The frequency of TIAEs was reduced in one center following implementation of an intubation checklist and a time-out procedure ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…We did observe a high rate of equipment failures as well as an association of equipment failures with TIAEs. Quality improvement initiatives may improve success rates and reduce TIAEs ( 15 ). The frequency of TIAEs was reduced in one center following implementation of an intubation checklist and a time-out procedure ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mosier et al assessed the effectiveness of a high-fidelity simulation programme for critical care fellows and showed an improvement in first-attempt success from 74% before training to 82% after training 9. A retrospective study of paediatric emergency intubations reported conformance to an established process model was associated with higher success rates and less adverse events 10. A previous Australian study by Fogg et al 11 demonstrated successful implementation of their airway bundle (including staff training and standardisation of equipment and practice) with improved first-attempt success rate from 83.4% to 93.9%.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, successful initiatives with similar interventions have been reported in other settings, albeit over a shorter time frame. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also generally consistent with the literature on improving the performance of emergency intubation. [11][12][13][14][15][16][17] These studies took a similar, checklist-or algorithm-based approach, and the magnitude of improvement was comparable. None of these studies, however, examined performance for more than 24 months.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%